Improving Student Learning Outcomes through Contextual Approach based on Learning Community - Iman, Syatanul; Herayanti, Lovy; Gummah, Syifa?ul (Lensa : Jurnal Kependidikan Fisika, 2019)
This study aims to improve student learning outcomes through the implementation of contextual approaches based on learning community in SMP Negeri 3 Tanjung in 2017/2018 Academic Year. This research is a classroom action research. Actions are carried out through two cycles, each cycle consisting of the process of planning, implementation, observation, and reflection. The instrument used was a multiple-choice test instrument. The subjects of this study were 26 students of class VIII-4 of SMP Negeri 3 Tanjung. The results of the study showed that in the cycle I the percentage of completeness of student learning outcomes was 76% with an average score of 74.23, while in the cycle II the percentage of completeness of student learning outcomes was 92% with an average score of 85.34. Based on the results of the study it can be concluded that the implementation of contextual approaches based on learning community can improve student learning outcomes.